The The Development of Teaching Materials for Recount Text Writing Skill Using Past Tense Based on Creative, Active, Systematic, And Effective (CASE) - Claudia, Dinny; Gaffar, Muhammad Andriana; Ruswandi, Riki (Universitas Islam Negeri Palopo, 2025)
This research aims to develop recount text writing teaching materials for sixth-grade students at SDN Permata Biru, focusing on mastering the past tense thru the CASE approach (Creative, Active, Systematic, and Effective). This study was motivated by students’ low writing ability, mainly due to limited mastery of past tense and low engagement in learning. This research applies a quantitative quasi-experimental design (One Group Pre-test and Post-test) involving 34 students. The research instruments include a writing test, a scoring rubric, and a student engagement observation sheet. The results show that students’ writing ability improved significantly after using CASE-based materials. The average pre-test score of 66.62 increased to 77.32 on the post-test. The paired sample t-test showed a significance value of p = 0.000 (p < 0.05), which means there was a significant difference between the pre-test and post-test results. An N-Gain value of 0.34 indicates a moderate improvement. The observation results also show that students become more active and enthusiastic in the learning process. Thus, CASE-based recount text writing materials have proven effective in improving students' writing abilities, particularly in the use of past tense and systematic text organization. Practically, this approach can serve as an alternative for teachers in creating creative, active, and meaningful writing lessons in elementary school.